Should minors and young adults qualify as potential live kidney donors? The views of international transplant professionals. (20th June 2019) - Thys, Kristof; Borry, Pascal; Schotsmans, Paul; Dobbels, Fabienne
Abstract: Although live kidney donation (LD) has become an increasingly common procedure, European and US transplant centres disagree as to whether minors and young adults should qualify as donor candidates. Therefore, we aimed to better understand the attitudes and viewpoints of transplant professionals. We conducted fourteen in‐depth interviews with a purposive sample of international transplant professionals from various professional backgrounds. Data analysis was guided by QUAGOL, a systematic approach based on the constant‐comparative method. Professionals expressed a cautionary view, worrying about the uncertain long‐term medical and psychosocial consequences of LD at a young age. They also worried that young individuals' decisions are more likely to be influenced by their psychosocial developmental stage or family pressure. As these concerns were more significant for minors as compared to young adults, minors were deemed ineligible for LD except for in highly exceptional circumstances. Professionals' attitudes were also influenced by the expected benefits for the recipient and the availability of therapeutic alternatives, as well as the strength of the donor‐recipient relationship. More prospective research on the long‐term medical and psychological outcomes in young adult donors is likely to shed more light on the acceptability of LD by adolescents and young adults.